Prospective study of propellar flaps vs. traditional local flaps in lower limb trauma reconstruction - Reddy, Praveen Kumar C. V.; Mucherla, Naga Teja (International Surgery Journal, 2022)
Background: Adequate coverage of traumatic complex lower extremity wounds is often challenging for reconstructive surgeons. Propeller perforator flaps have gained wide acceptance as an alternative in soft tissue coverage of complex lower extremity defects over the last decade. We report our experience with distal lower extremity reconstructions performed either with traditional local flaps vs. propeller perforator flaps. our aim here was to compare non-microvascular flaps with traditional local flaps for coverage of traumatic lower extremity wounds. Methods: 30 patients operated for lower extremity defects and reconstructed either with traditional local flaps or propeller perforator flaps between November 2016 to December 2020 were included in the study. Results: There were 22 male and 8 female patients. Mean age was 43.00±14.85 (range: 24 to 66 years) in the local flap group and mean age was 42.11±12.05 (range: 23 to 65 years) in the propeller perforator flap group. Hospital stays and overall operation time was significantly higher in the propeller flap group. There was no statistically significant difference in complication rates between either group. Conclusions: Concerning many advantages, like decreased operative time, avoiding micro anastomosis, reconstruction with like tissues, we suggest that propeller perforator flaps can be first-line reconstructive choice. These flaps can be used successfully by reconstructive surgeons in small clinics to prevent unnecessary tertiary medical center referrals as well as extended hospitalizations, long operation times, and increased costs. However, propeller flaps do hold more complications compared to local flaps and do require technical expertise.